The effectiveness of cognitive therapy with acceptance and commitment in improving self-concept and reducing symptoms of obsessive-compulsive disorder Clinical study in Mouwasat Hospital in Damascus (Journal of Hama University, 2021)
This study aimed at identifying the effectiveness of cognitive therapy with acceptance and commitment in improving self-concept and reducing symptoms of obsessive-compulsive disorder in OCD patients attending the Psychological Division at the Mouwasat Hospital in Damascus. A patient was selected from them to document the treatment steps that were taken according to the qualitative method of the research.In the study, a therapeutic program based on the basic principles of acceptance and commitment therapy was used by the researcher. The Tennessee Scale for self-concept was also used, and the revised mental health scale SCL- 90- RThe results showed the effectiveness of acceptance and commitment therapy in OCD patients. The symptoms of disorder decreased and the self-concept improved in the case studied on the scales used in the post application more than in the pre application.